Participation Training: A Model for Experiential Learning - María del Carmen Rodríguez (Adult Education Research Conference, 2004)
This paper introduces the principles of Participation Training (PT) within the frame of Freire’s (1970) notion of Education for Liberation and presents implications for the development of adult education, theory, and practice.